DIEL CHANGES IN THE VERTICAL DISTRIBUTION AND FEEDING ACTIVITY OF COPEPODS IN ICE-COVERED RESOLUTE PASSAGE, CANADIAN ARCTIC (EXTENDED ABSTRACT) (16th Symposium on Polar Biology) - ハットリ, ヒロシ; サイトウ, ヒロアキ; HATTORI, Hiroshi; SAITO, Hiroaki (National Institute of Polar Research, 1995)
P(論文) departmental bulletin paper